Rapid Assesmen Manajemen Instalasi Gawat Darurat RSUT pada Pandemi Covid-19 - Tita Maulita Sawitri; Pujiyanto Pujiyanto (Jurnal Health Sains, 2021)
Covid-19 caused changes in services related to procedures, facilities, procedures and safety of patients and officers in work. RSU Tangerang Regency (RSUT) is one of the government-owned hospitals appointed to provide services for Covid-19 patients throughout its service scope. RSUT has made changes in the management of IGD services, especially in patient triage to adjust for changes in current disease patterns. The purpose of this study is to find out the rapid assessment of emergency department management management in the covid-19 pandemic. This paper is the result of a rapid assessment of service observations at IGD RSUT in June 2020, accompanied by interviews to igd management teams and hospitals. This study is a case study by conducting rapid assessment of services at the Emergency Department of RSU Tangerang Regency during June 2021. The results of the observations showed that IGD RSUT had made changes in accordance with the ministry's guidelines on hospital services during the covid-19 pandemic, only adding thoracic radiological examinations as part of screening.